Notary's Prudence Duty Effectiveness in Indonesian Financing Deeds: BPRS Rifat Case - Salma Nur Azizah; Reka Dewantara; Dewi Iryani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Marital property separation agreements are governed by Article 29 of Law Number 1 of 1974 on Marriage and Articles 139–148 of the Indonesian Civil Code, which originally restricted their execution to the period prior to marriage. The issuance of Constitutional Court Decision Number 69/PUU-XIII/2015, however, permits postnuptial amendments with court approval, thereby generating legal uncertainty regarding the legal status of marital assets and inconsistencies in judicial decisions. This study aims to examine the legal status of joint property acquired prior to the amendment of a marital agreement following the Constitutional Court’s decision and to analyze the legal implications of amendments or annulments of marital agreements on the position and distribution of marital property. This research employs a normative juridical method with statutory, conceptual, and case approaches, conducted through library research of primary legal materials, including marriage legislation, the Civil Code, and relevant court decisions, as well as secondary and tertiary legal materials. The data are analyzed qualitatively using a descriptive-analytical approach. The results indicate that marital property acquired prior to the amendment of a marital agreement is subject to prospective application and does not have retroactive effect, thereby maintaining its original legal status in accordance with the principle of legal certainty. Furthermore, the study underscores the necessity of implementing regulations to ensure uniformity in notarial and judicial practices and to promote distributive and corrective justice.